Strong enhancement of parity violation effects in chiral uranium compounds - Wormit, Michael; Olejniczak, Małgorzata; Deppenmeier, Anna-Lena; Borschevsky, Anastasia; Saue, Trond; Schwerdtfeger, Peter (Physical chemistry, chemical physics, 2014)
The effects of parity violation (PV) on the vibrational transitions of chiral uranium compounds of the type NUXYZ and NUHXY (X, Y, Z = F, Cl, Br, I) are analysed by means of exact two-component relativistic (X2C) Hartree-Fock and density functional calculations using NUFClI and NUHFI as representative examples. The PV contributions to the vibrational transitions were found to be in the Hz range, larger than for any of the earlier proposed chiral molecules. Thus, these systems are very promising candidates for future experimental PV measurements. A detailed comparison of the NUHFI and the NWHFI homologues reveals that subtle electronic structure effects, rather than exclusively a simple Z5 scaling law, are the cause of the strong enhancement in PV contributions of the chiral uranium molecules.
Gesehen am 28.07.2020